ANALISIS TINGKAT KEPUASAN PELANGGAN DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) PADA ONLINE SHOP SHOPEE (STUDI KASUS PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NUSANTARA PGRI KEDIRI) - Anggini, Anggini; Subagyo, Subagyo; Widodo, Moch Wahyu (Universitas Nusantara PGRI Kediri, 2022)
This purpose of this research is to asccertain the level of customer satisfaction at the Shopee online shop. The research approach used is quantitative and is a descriptive type of research. The population used in this research were students of the Faculty of Economics and Business, Universitas Nusantara PGRI Kediri. The sample was determined by 92 students who were taken using the simple random sampling method. Collecting data make use of questionnaire which is then analyzed using Importance Performance analysis. The results of this study are that there are still some student customers who are not fulfil with the services provided by Shopee based on 5 dimensions of service quality in direct evidence (tangible), responsiveness (responsiveness) , reliability (reliability), concern ( empathy) and assurance (assurance).